2013
DOI: 10.1152/ajpgi.00334.2012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of L-FABP and glucose on polyunsaturated fatty acid induction of PPARα-regulated β-oxidative enzymes

Abstract: . Impact of L-FABP and glucose on polyunsaturated fatty acid induction of PPAR␣-regulated ␤-oxidative enzymes. Am J Physiol Gastrointest Liver Physiol 304: G241-G256, 2013. First published December 13, 2012; doi:10.1152/ajpgi.00334.2012.-Liver fatty acid binding protein (L-FABP) is the major soluble protein that binds very-long-chain n-3 polyunsaturated fatty acids (n-3 PUFAs) in hepatocytes. However, nothing is known about L-FABP's role in n-3 PUFA-mediated peroxisome proliferator activated receptor-␣ (PPAR␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 130 publications
0
52
0
Order By: Relevance
“…Increasingly, however, FABPs are emerging as specific mediators of precise signaling pathways. For instance, FABP1 facilitates the polyunsaturated fatty acid and fibrate-induced transactivation of PPAR␣, via direct interaction with the nuclear receptor's ligand binding domain (15)(16)(17). A similar role has been observed with FABP4, whereby its ligand-mediated dimerization state governs nuclear import and subsequent ligand delivery to PPAR␥ (18,19).…”
mentioning
confidence: 81%
“…Increasingly, however, FABPs are emerging as specific mediators of precise signaling pathways. For instance, FABP1 facilitates the polyunsaturated fatty acid and fibrate-induced transactivation of PPAR␣, via direct interaction with the nuclear receptor's ligand binding domain (15)(16)(17). A similar role has been observed with FABP4, whereby its ligand-mediated dimerization state governs nuclear import and subsequent ligand delivery to PPAR␥ (18,19).…”
mentioning
confidence: 81%
“…Restoration of hepatic FABP1 by receiving a fi sh oil diet was associated with lowered serum triglycerides and VLDL cholesterol levels and elevated serum high density lipoprotein cholesterol levels, as well as downregulated expression of TNF-␣ and IL-6, in livers of diabetic rats ( 94 ). FABP1 ablation significantly impacted hepatic fatty acid ␤ -oxidative genes mediated by PPAR ␣ activation of the dietary n-3 PUFAs (rich fi sh oil), an even more prominent effect in the context of high glucose ( 95 ). Higher dose alcohol consumption is associated with impaired peroxisomal ␤ -oxidation and FABP1 responses to PPAR ␣ in rats, and the severity of fatty liver correlated inversely with the level of FABP1.…”
Section: Fabp1 As a Cellular Antioxidantmentioning
confidence: 98%
“…Several studies have shown that L-FABP mediates the effects of exogenous FAs, especially polyunsaturated FAs, on PPAR-␣ gene expression and activity ( 17,42,43 ). L-FABP physically interacts with PPAR-␣ and it is thought that this interaction facilitates transfer of FA ligands ( 18 ).…”
Section: L-fabp Deletion Does Not Mediate the Effects Of Atgl Knockdomentioning
confidence: 99%